Solve each of these systems using the substitution method. Make sure to check your answers !
2x + 3y = -4

x āˆ’ 2y = 5

a. x = 1, y = -2

b. x = -1, y = 2

c. x = 1, y = 2

d. x = -2, y = -1

Respuesta :

Answer:

a. x = 1, y = -2

Step-by-step explanation:

The given equations are 2x + 3y = -4 -------------(1)

x - 2y = 5 -----------------(2)

From the second equation, we get x = 2y + 5

Now plug in x = 2y + 5 in the first equation, we get

2(2y + 5) + 3y = - 4

4y + 10 + 3y = -4

7y + 10 = -4

7y = -14

y = -2

Now plug in y = -2 in x = 2y + 5 to find the x value.

x = 2(-2) + 5

x = -4 + 5

x = 1

Therefore, x = 1, y = -2

Thank you.

ACCESS MORE